Preserving the Authenticity of the Quranic Recitation: The Importance of Sanad Lineage at Tahfiz Boarding School in South Kalimantan - Ahyar Rasyidi (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
This study aims to explain and analyze the reading Sanad of tahfiz Al-Qur'an Islamic Boarding Schools in South Kalimantan. This study uses a phenomenological approach as proposed by Alfred Schutz and Peter L Berger. The goal of the phenomenological approach is to understand everyone's beliefs, including the most controversial interpretations within the tradition. Phenomenology does not attempt to analyze or explain an event, but the basic concept of phenomenology is meaning. Based on the research findings, that in South Kalimantan, in general, the tahfiz Al-Qur'an boarding school received a channel for reading through the Al-Qur'an education they had previously attended, or the boarding school where they became students. Although there are some ustaz who are not willing to reveal the path of their reading chain, and some others do not yet have a reading chain. The dynamics of the sanad and the methods used in the tahfiz Al-Qur'an Islamic boarding school in South Kalimantan, are not much different from other regions. The talaqqi or encounter method, is the isnad line that is often used in every tahfiz Al-Qur'an boarding school in South Kalimantan, the genealogy of the Al-Qur'an reading owned by the teachers, was obtained from their previous kiai, that is, from the kiai at the Islamic boarding school where they recited and memorized the Qur'an previously, then passed it down by talaqqi to their students, of course, who have met the agreed conditions and become the rules for giving sanad at each tahfiz Al-Qur'an Islamic boarding school.